2016
DOI: 10.17240/aibuefd.2016.16.2-5000194950
|View full text |Cite
|
Sign up to set email alerts
|

3-6 Yaş Çocuklarının Tercih Ettikleri Çizgi Filmlerdeki Şiddet İçeriklerinin Analizi

Abstract: ÖZETBu çalışmanın amacı okul öncesi eğitimine devam eden 3-6 yaş çocuklarının televizyonda en çok izledikleri çizgi filmleri tespit etmek, bu çizgi filmlerdeki şiddet içeriklerinin oranlarını belirlemektir. Araştırma, içerik analizi yoluyla yapılmıştır. Çocukların en çok tercih ettiği çizgi filmlere ilişkin veriler, 2015 yılının Nisan ayında Ankara ilinde yer alan orta sosyoekonomik düzeydeki bir anaokulundan öğretmenler aracılığı ile çocuklara sorularak anket yoluyla toplanmıştır. Çocukların en çok tercih ett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…Çizgi film ile ilgili yapılan çalışmalar incelendiğinde çizgi filmlerde sıklıkla, kurallara uymama, şiddet, cinsiyet ayrımı gibi konuların yer aldığı ve iyi-kötü, kuvvetli-zayıf gibi özelliklere yoğun biçimde vurgu yapıldığı görülmektedir (Kolojarceva, andArtemyeva, 2017, p.1272;Temizyürek ve Acar, 2014, s.34;Özen ve Kartelli, 2017, s.81;Muslu, 2015, s.61;Kara, 2016, s.20;Yıldız, 2016, s.698, Pazarbaşı, 2018Özdemir ve Ramazan, 2012, s.160;Rai, Waskel, Sakalle, Dixit, andMahore, 2017, p.1376).…”
Section: Introductionunclassified
“…Çizgi film ile ilgili yapılan çalışmalar incelendiğinde çizgi filmlerde sıklıkla, kurallara uymama, şiddet, cinsiyet ayrımı gibi konuların yer aldığı ve iyi-kötü, kuvvetli-zayıf gibi özelliklere yoğun biçimde vurgu yapıldığı görülmektedir (Kolojarceva, andArtemyeva, 2017, p.1272;Temizyürek ve Acar, 2014, s.34;Özen ve Kartelli, 2017, s.81;Muslu, 2015, s.61;Kara, 2016, s.20;Yıldız, 2016, s.698, Pazarbaşı, 2018Özdemir ve Ramazan, 2012, s.160;Rai, Waskel, Sakalle, Dixit, andMahore, 2017, p.1376).…”
Section: Introductionunclassified
“…Results and Discussion: The results reported that the animated content on YouTube was partially suitable for the age of the child and that these contents partially supported cognitive and socialemotional development, but were completely insufficient in terms of supporting physical development. The probability of encountering inappropriate content in the cartoons that children watch most on TV (Yıldız, 2016) and on YouTube (Papadamou et al, 2019b) is substantial. That YouTube is the most used platform by children (Rideout & Robb, 2020) and that it is a part of children's lives from a very young age (Anderson, Auxier & Nolan, 2020;Marsh et al, 2019) indicates it contains content that will attract children's attention.…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Parvin and Islam (2020), it was pointed out that besides the positive effects of cartoons, they led children to have sight and hearing problems, harmed the imaginations, led to impairment of their mental and physical health, to attain superstitious ideas, to be affected by cultures, to learn telling lies, to increase the indifference towards multiway studies, to imagine themselves as cartoon characters, to have lack of attention, to guide toward violence and to have unintended behaviors and of sympathy and that they took the bad characters as a role model. In a study carried out by Yıldız (2016), it was pointed out that 14 mostly preferred cartoons by children at the age of 3-6 were watched 39.495 seconds in total and that violent elements comprised 4.220 seconds of the watching duration. In another study by Hassan and Daniyal (2013), it was found that violence was indispensable parts of even funny cartoons, the characters loved by children fought each other and there were fighting scenes between the two characters at 82.6% rate.…”
Section: Discussionmentioning
confidence: 99%